Pilot testing of enhanced sorbents for calcium looping with cement production - Erans, María; Jeremias, Michal; Zheng, Liya; Yao, Joseph G.; Blamey, John; Manovic, Vasilije; Fennell, Paul S.; Anthony, Edward J. (Elsevier, 2018)
One of the main challenges for commercialising calcium looping (CaL) as a CO2 capture technology is maintaining a high level of sorbent reactivity during long-term cycling. In order to mitigate the decay in carrying capacity, research has moved towards producing enhanced sorbents. However, this creates potential problems related to ease of scaling up production techniques and production costs, and raises the question as to whether such approaches can be used at large scale. On the other hand, a key advantage of CaL over other carbon capture technologies is synergy with the cement industry, i.e., use of spent sorbent as a feedstock for clinker production. In this work two enhanced materials: (i) limestone doped with HBr through a particle surface impregnation technique; and (ii) pellets prepared from limestone and calcium aluminate cement, were tested in a 25 kWth dual fluidised bed pilot-scale reactor in order to investigate their capture performance and mechanical stability under realistic CaL conditions. Moreover, the spent sorbent was then used as a raw material to make cement, which was characterised for phase and chemical composition as well as compressive strength. The HBr-doped limestone showed better performance in terms of both mechanical strength and stability of the CO2 uptake when compared to that of pellets. Furthermore, it was shown that the cement produced has similar characteristics and performance as those of commercial CEM 1 cement. This indicates the advantages of using the spent sorbent as feedstock for cement manufacture and shows the benefits of synthetic sorbents in CaL and suitability of end-use of spent sorbents for the cement industry, validating their synergy at pilot scale. Finally, this study demonstrates the possibility of using several practical techniques to improve the performance of CaL at the pilot scale, and more importantly demonstrates that commercial-grade cement can be made from the lime product from this technology.
Keywords: Calcium looping; CCS; Pilot plant; Cement